A Checklist of Cicadidae (Insecta: Hemiptera) from Vietnam, with Some Taxonomic Remarks - Lee, Young June (Zootaxa, 2008)
This paper provides the first checklist of Cicadidae (Hemiptera) from Vietnam, comprising 111 species belonging to 36 genera. In addition, the following taxonomic changes are proposed: Aola Distant, 1905 syn. nov. is synonymized with Haphsa Distant, 1905; Cicada orientalis (Distant, 1912) is transferred to Pomponia Stål, 1866 to become Pomponia orientalis (Distant, 1912) comb. nov.; Pomponia scitula Distant, 1888 and Aola bindusara (Distant, 1881) are transferred to Haphsa Distant, 1905 to become Haphsa scitula (Distant, 1888) comb. nov. and Haphsa bindusara (Distant, 1881) comb. nov.; Platylomia divergens (Distant, 1917), Platylomia assamensis Distant, 1905, Platylomia diana Distant, 1905, Platylomia saturata (Walker, 1858) and Platylomia pieli Kato, 1938 are transferred to Macrosemia Kato, 1925 to become Macrosemia divergens (Distant, 1917) comb. nov., Macrosemia assamensis (Distant, 1905) comb. nov., Macrosemia diana (Distant, 1905) comb. nov., Macrosemia saturata (Walker, 1858) comb. nov. and Macrosemia pieli (Kato, 1938) comb. nov.; Cryptotympana corvus (Walker, 1850) is removed from the Vietnamese fauna because this record is thought to have been based on a misidentification. Taxonomic remarks and information on geographic distributions are also provided.